Seksualiteit en cultuurstrijd: Een theologisch voorstel tot dialoog - de Bruijne, Ad (Religie & Samenleving, 2016)
This article contends that the culture war between orthodox Christians and late modern propagators of sexual emancipation should be abandoned in favour of a constructive dialogue. Such a dialogue becomes possible when we no longer presuppose a break between the late modern and the traditional Christian narrative but conceive of both as closely related and even interconnected. Building on the work of authors such as Charles Taylor and Oliver O’Donovan this is demonstrated with respect to some features of late modern sexuality. Against that background some proposals are made to illustrate how a dialogue with the ‘opposing’ party would, in fact, be profitable to both.